(untitled) (Journal of actual problems of jurisprudence, 2025)
In contemporary Kazakhstan, the adaptation of labor relations involves harmonizing the interests of various societal stakeholders through globalization and international integration, with the aim of maintaining stability and fostering socio-economic growth. This study examines the characteristics and complexities of labor relations among the government, workers, and employers in Kazakhstan. Employing analysis and synthesis methods, the research investigates the concept of dialogue and partnership in legislative scrutiny of labor laws, while also assessing the level of participation from government, employers, and employees in this process. The dialogue perspective is used to develop a unified understanding of dialogue as a process where employers, employees, and authorities interact to reach agreements on labor-related issues such as working conditions and social welfare. Kazakhstan’s Labor Code specifically outlines regulations for labor relations, including rights and responsibilities of employers and workers, protection against discrimination, and workplace monitoring. Public opinion on the roles of authorities, workers, and employers in dialogue varies, influenced by factors such as respondents’ age and industry. In the IT and communications sectors, many workers perceive a lack of management engagement. Employee involvement levels also differ, with perceptions varying by gender. The practical significance of this research lies in its potential to inform national policy changes that could enhance social stability and economic growth. Furthermore, the study’s findings may contribute to improving interactions between employers, employees, and the government, thereby promoting social stability and economic progress. Keywords: labor law, social dialogue, social partnership, sectoral differences, harmonization of interests.